Information quality and market efficiency - Thomas, S.Y. Ho; Michaely, Roni; Salomon Brothers Center for the Study of Financial Institutions (New York: Salomon Brothers Center for the Study of Financial Institutions, 1986)
The paper analyzes the optimal individual behavior in acquiring information and determines the amount of information incorporated in a stock at equilibrium in the presence of a cost schedule in acquiring information.
Working Paper Series: Number 403
Incudes bibliographical references
rua 21/04/17
Loans
Keywords: Stocks--Prices; Information theory in economics